2022
DOI: 10.1002/admt.202200260
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Slip Sensing Technology Based on the Conductive Sponge‐PVDF

Abstract: engineering applications, normal and shear force components are generated between the tactile sensor and the object when sensing the object's motion. [2] To extract the required data, the tactile sensor should have a good dynamic response to track oscillatory variations of normal and shear forces in real-time. Recently, sensors have been developed to detect the shear force. According to the detection principle, tactile sensors can be mainly divided into capacitive, [3][4][5] piezoresistive, [6,7] triboelectric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…The primary goals of current piezoelectric tactile sensor research on PVDF-based materials are to increase PVDF's piezo-electric sensitivity and piezoelectric conversion efficiency. [55] On the one hand, the polarization of PVDF is accomplished by treatments such as stretching polarization, or by using processes such as electrostatic rotation during the application of high voltage. Mainly because the 𝛽-phase as the main piezoelectric phase, through processes such as stretching can transform the stable 𝛼phase into 𝛽-phase to improve its performance (see Section 2.3 for details of the transformation), and the high voltage applied during electrostatic spinning will align the dipoles in PVDF, and its mechanical strength can form a strong fiber network, effectively loading the polymer to form the 𝛽-phase, and during the application of pressure the structure is more stable and The piezoelectric properties are improved.…”
Section: Pvdf Flexible Piezoelectric Tactile Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary goals of current piezoelectric tactile sensor research on PVDF-based materials are to increase PVDF's piezo-electric sensitivity and piezoelectric conversion efficiency. [55] On the one hand, the polarization of PVDF is accomplished by treatments such as stretching polarization, or by using processes such as electrostatic rotation during the application of high voltage. Mainly because the 𝛽-phase as the main piezoelectric phase, through processes such as stretching can transform the stable 𝛼phase into 𝛽-phase to improve its performance (see Section 2.3 for details of the transformation), and the high voltage applied during electrostatic spinning will align the dipoles in PVDF, and its mechanical strength can form a strong fiber network, effectively loading the polymer to form the 𝛽-phase, and during the application of pressure the structure is more stable and The piezoelectric properties are improved.…”
Section: Pvdf Flexible Piezoelectric Tactile Sensorsmentioning
confidence: 99%
“…Currently, there are relatively few multifunctional tactile, tactile sensors that have been developed, most of which can only detect one quantity and have some shortcomings in performance. Wang [55] compared the performance of piezoelectric tactile sensors prepared by conductive sponge with RTV silicone rubber substrate and PDMS substrate as substrates, and the results showed that RTV silicone rubber and PDMS, as insulating materials, hindered the charge output of PVDF films. It is noteworthy that the porous mesh structure of the conductive sponge allows PVDF to produce higher piezoelectric output, but the detection amount is still relatively single and can only sense the magnitude direction of the slip force.…”
Section: Pvdf Copolymer Flexible Piezoelectric Tactile Sensorsmentioning
confidence: 99%
“…Such nonlinearity in the figure may be caused by the enhancement of stiffness of the ferroelectret layer of the FCSs at high applied pressures which is often observed in ferroelectret films. [25] To improve the linearity of the FCSs, an extension of the elastic modulus range in the ferroelectret films is expected, which could be achieved by optimizing the mechanical cellular structure in the films. However, this topic is beyond the scope of this article and relevant work will be published in future papers.…”
Section: Charge Generated and Sensitivity Of Fcssmentioning
confidence: 99%
“…1D threadlike electromechanical sensors include functional fibers [5,11,15,16] and piezoelectric wire/cable sensors. [17][18][19] The adopted mechanisms in them involve piezoresistance, [20,21] capacitance, [7,22,23] piezoelectricity, [24,25] and triboelectricity. [26] Regarding power consumption, the sensors based on triboelectric structures and piezoelectric materials are superior to the piezoresistance and capacitance-based sensors because no external power supply is needed.…”
Section: Introductionmentioning
confidence: 99%